Voices of teacher candidates of color on white race evasion: 'I worried about my safety!'. Issue 8 (13th September 2016) - Amos, Yukari Takimoto
Abstract: This qualitative study investigated the negative impacts minority teacher candidates receive from white teacher candidates in a required multicultural education class. The findings reveal that four teacher candidates of color had difficulty positioning themselves among the overwhelming silencing power of whiteness in the class. The white students were tactful at evading power and race and flattening the existing hierarchical power relations through the discourses of colorblindness and by preying on the minority instructor. Their understanding of diversity was also shallow. On the other hand, the teacher candidates of color were afraid that they might be labeled as the ones who spoke up against the white students and fearful of the possibility of retaliation and ostracism from the white peers. It seems that the teacher education program's structure allowed the white candidates to impose strong negative peer pressure on the teacher candidates of color.